The role of local government in sports development in Maros district - Arman Arman (Requisitoire Law Enforcement, 2022)
This study aims to determine and analyze the role Regional Government in Sports Development in Maros Regency and what factors influence Sports Development in Maros Regency. Qualitative analysis techniques, namely data analysis based on words arranged in the form of expanded text. The data analyzed are data from situations or events that occur in the field and are also supported with the help of primary data derived from interviews, questions, responses from informants and literature studies based on the indicators determined in the study. The results of the study show that the role of the Sports and Arts Youth Service in coaching athletes in Maros district, can be seen from the implementation of the main tasks and functions of the Maros Regency Sports and Arts Youth Service. In accordance with the author's observations in the field, it can be seen that coaching for athletes in Maros Regency is not sustainable. Athletes only get awards and various services when there is a championship event, after the event is over and there are no more championships, athletes are generally no longer cared for and will be looked for when there is another championship. This is an important task for local governments in general and the Youth and Sports Service in particular so that there would be special guarantees for athletes who have made the name of the region proud. The supporting factors for sports development are the high interest and talent of sports athletes and the presence of professional trainers in Maros district. While the inhibiting factor is the lack of funds and facilities and infrastructure for the sports coaching process in Maros district.